Combatting Climate Change in the Pacific The Role of Regional Organizations - Williams, Marc (Springer International Publishing, 2018)
This book analyses the regional complexes of climate security in the Pacific. Pacific Island States and Territories (PICTs) have long been cast as the frontline of climate change and placed within the grand architecture of global climate governance. The region provides compelling new insights into the ways climate change is constructed, governed, and shaped by (and in turn shapes), regional and global climate politics. By focusing on climate security as it is constructed in the Pacific and how this concept mobilises resources and shapes the implementation of climate finance, the book provides an up-to-date account of the way regional organizations in the Pacific have contributed to the search for solutions to the problem of climate insecurity. In the context of the United Nations Climate Change Conference (COP21) in Paris in 2015, the focus of this book on regional governance offers a concise and innovative account of climate politics in the prevailing global context and one with implications for the study of climate security in other regions, particularly in the developing world.